2010
DOI: 10.1091/mbc.e09-08-0743
|View full text |Cite
|
Sign up to set email alerts
|

Folding-competent and Folding-defective Forms of Ricin A Chain Have Different Fates after Retrotranslocation from the Endoplasmic Reticulum

Abstract: This study reveals that components of the yeast ERAD-L pathway can discriminate between two subtly different forms of the same toxin substrate. Although precytosolic requirements are similar for both toxin structures, there is a divergence in fate on the cytosolic face of the ER membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(134 citation statements)
references
References 75 publications
7
126
1
Order By: Relevance
“…Although our results indicate that they have redundant functions, this does not exclude the possibility that they also have their specific cargo proteins. Li et al (75) identified erp2⌬ by screening for resistance to exogenously expressed ricin A-chain. When the toxin is expressed in yeast and targeted to the ER lumen, it is translocated back to the cytosol and exhibits cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although our results indicate that they have redundant functions, this does not exclude the possibility that they also have their specific cargo proteins. Li et al (75) identified erp2⌬ by screening for resistance to exogenously expressed ricin A-chain. When the toxin is expressed in yeast and targeted to the ER lumen, it is translocated back to the cytosol and exhibits cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…RTA has relatively minor requirements for Usa1p, Cue1p and Ubx7p and shows no requirements for Yos9p functions. Furthermore, RTA dislocation is independent of the E3 activity of Hrd1p (Li et al 2010). ER dislocation of RTA in plant cells is also independent of canonical ubiquitylation (Marshall et al 2008).…”
Section: Dislocation Across the Er Membranementioning
confidence: 93%
“…The initial remodelling of RTA after subunit reduction may therefore explain why, when expressed in the yeast ER, maximal toxicity of RTA requires the co-chaperones of Kar2p, the yeast equivalent of BiP (Li et al 2010) and rationalise a proposed role for the Hsp90 family ER chaperone GRP94 in ricin toxicity to mammalian cells (Spooner et al 2008a;Taylor et al 2010). …”
Section: Maintenance Of Solubility and Recognition As Substrates For mentioning
confidence: 99%
See 2 more Smart Citations